Comparative Gender and Institutions: Directions for Research - Chappell, Louise (Perspectives on Politics, 2010)
A comparative politics of gender offers an opportunity to consider in detail the operation of gender within political institutions. As such, it contributes to a deeper understanding of the roles and experiences of men and women within political institutions, of the policies, laws and norms that are the outcomes of these institutions, and of the relationship between these institutions and social actors. This essay proposes a multi-directional strategy for undertaking comparative gender and institutional research that includes taking account of similarities and differences within and across states, between states and international institutions, across space as well as across time. It argues that through this research strategy it is possible to gain a more nuanced understanding of gender processes and outcomes, which is valuable to those working both inside and outside political institutions to advance a women's equality agenda.
Publisher: Cambridge University Press